Natterin bridges IFN-φ1 and non-canonical inflammasome pathways via CRFB1/Gbp4 to license Caspy2-mediated antibacterial immunity - Gusso, Darlan; Pinto, Felipe Justiniano; Andrade-Barros, Aline Ingrid; Bernardo, Jefferson Thiago Gonçalves; DeOcesano-Pereira, Carlos; Lopes-Ferreira, Monica; Lima, Carla (Frontiers in Cellular and Infection Microbiology, 2025)
The Natterin protein family represents an evolutionarily conserved group of immune effectors in teleosts, yet its broader regulatory role in host defense remains poorly understood. Here, we demonstrate that Natterin functions as a master upstream regulator, orchestrating a critical immune network that integrates type I interferon (IFN-I) signaling with non-canonical inflammasome activation during Salmonella Typhimurium (ST) challenge. Using wild-type embryos treated with IFN-I neutralizing antibody followed by the use of natterin (loc795232) knockout (KO) embryos generated by CRISPR/Cas9 and integrated approaches—including RT-qPCR, Western blotting, immunohistochemistry, and behavioral assays—we found that its absence completely abrogates the ST-induced IFN-I response, including the ablation of the interferon regulatory factors irf3 and irf7 and the IFN-φ1 receptor crfb1. Consequently, Natterin deficiency prevented the expression of the LPS sensor GBP4 and the proteolytic maturation of the inflammatory caspases Caspy and Caspy2. This disruption abolished downstream gsdme-a/b expression, which may result in the non-formation of pores. The critical role of IFN-I signaling was independently confirmed by its neutralization in wild-type embryos, which abolished the protein-level localization of IL-1β and IFN-β and mirrored the KO phenotype. Functionally, this disruption led to a sixfold increase in mortality and exacerbated ST-induced pathogenesis. Our results establish Natterin not merely as an effector molecule but as a pivotal regulator that integrates IFN-I and inflammasome signaling, orchestrating a coordinated immune response essential for host survival. This work reveals a previously unrecognized level of regulation in teleost innate immunity with significant evolutionary parallels to mammalian defense mechanisms.